Distribuição de conteúdos em redes veiculares usando mecanismos de comunicação tolerantes ao atraso - Pessoa, Gonçalo da Silva (2018)
The last couple of decades have been the stage for the introduction of new telecommunication networks. It is expected that in the future all types of vehicles, such as cars, buses and trucks have the ability to intercommunicate and form a vehicular network. Vehicular networks display particularities when compared to other networks due to their continuous node mobility and their wide geographical dispersion, leading to a permanent network fragmentation. Therefore, the main challenges that this type of network entails relate to the intermittent connectivity and the long and variable delay in information delivery. To address the problems related to the intermittent connectivity, a new concept was introduced – Delay Tolerant Network (DTN). This architecture is built on a Store-Carry-and-Forward (SCF) mechanism in order to assure the delivery of information when there is no end-to-end path deﬁned. Vehicular networks support a multiplicity of services, including the transportation of non-urgent information. Therefore, it is possible to conclude that the use of a DTN for the dissemination of non-urgent information is able to surpass the aforementioned challenges. The work developed focused on the use of DTNs for the dissemination of non-urgent information. This information is originated in the network service provider and should be available on mobile network terminals during a limited period of time. In order to do so, four diﬀerent strategies were deployed: Random, Least Number of Hops First (LNHF), Local Rarest Bundle First (LRBF) e Local Rarest Generation First (LRGF). All of these strategies have a common goal: to disseminate content into the network in the shortest period of time and minimizing network congestion. This work also contemplates the analysis and implementation of techniques that reduce network congestion. The design, implementation and validation of the proposed strategies was divided into three stages. The ﬁrst stage focused on creating a Matlab emulator for the fast implementation and strategy validation. This stage resulted in the four strategies that were afterwards implemented in the DTNs software Helix – developed in a partnership between Instituto de Telecomunicac¸˜oes (IT) and Veniam R , which are responsible for the largest operating vehicular network worldwide that is located in Oporto city. The strategies were later evaluated on an emulator that was built for the largescale testing of DTN. Both emulators account for vehicular mobility based on information previously collected from the real platform. Finally, the strategy that presented the best overall performance was tested on a real platform – in a lab environment – for concept and operability demonstration. It is possible to conclude that two of the implemented strategies (LRBF and LRGF) can be deployed in the real network and guarantee a signiﬁcant delivery rate. The LRBF strategy has the best performance in terms of delivery. However, it needs to add a signiﬁcant overhead to the network in order to work. In the future, tests of scalability should be conducted in a real environment in order to conﬁrm the emulator results. The real implementation of the strategies should be accompanied by the introduction of new types of services for content distribution.